The repositioning and urbanisation of health: new healthy places along hospital-city-continuum and its implications for healthy city planning - Maierhofer, Magdalena (AESOP, 2019)
The role of health in our cities and in planning is radically changing. Aaron Antonovsky’s concept of the Healthease-Disease-Continuum brought the dichotomy of disease and health to an end. Consequently, the differentiation between a place for the ill (hospital) and one for the healthy (neighbourhood) is outdated and rather moves towards into a Hospital-City-Continuum. While the World Health Organisation (WHO) identified the city and the urban environment as the main setting for health promotion, health infrastructures are gradually losing their insulated positions and turn into integrated elements of the neighbourhood’s everyday life. Considered systematically the borders between hospital- and urban areas are blurring. Resulting from this, new fields and places for health infrastructure, health promotions and urban health evolve. At the same time, health promotion and health care increasingly penetrate the everyday spaces in the cities. Digital Health, individualized care, personalised (or stratified) medicine and mobile medical devises are no longer banded to health institutions. On the contrary, they can turn a private bedroom into a temporary patient room. The paper identifies and describes these (new) healthy places, positions them along the Continuum and enquires into their possible futures.
Keywords: health; cities; hospital; WHO; health infrastructures